Improving the Listening Skills of Tadris Students in English Through the Film Animation Application - Hendriyanto Bujangga (Institut Agama Islam Negeri Imam Bonjol Padang, 2022)
This classroom action research aims to improve students' listening skills through the application of animated films. The subjects in this study were second semester students at STAIN Gajah Putih Takengon. The data in this study were obtained from observation sheets, tests and questionnaires. Based on the analysis that has been carried out, it is known that in cycle I, 68.57% of students are actively involved in learning and 70% of students are motivated and enthusiastic about learning. Whereas in cycle II, 77.14% of students were actively involved and 88.57% of students were motivated and enthusiastic about participating in learning. In the preliminary study, the average listening ability of students was 53.43%, in the first cycle the students' average listening ability increased to 59.37%, and in the second cycle the increase reached 76.71%. The results of the student response questionnaire showed that 87.5% felt happy with the application of animated films and 81.25% felt that the use of animated films had an effect on listening skills. 93.75% said it was easier to practice listening skills with animated films and 90.63% preferred learning to listen with animated films compared to other media such as tape recorders, and 93.75% disagreed with learning to listen without using audio visual aids.